Investigation of the Clinical Value of Four Visualization Modalities for Congenital Heart Disease - Lee, Shen-yuan; Squelch, Andrew; Sun, Zhonghua (MDPI, 2024)
Diagnosing congenital heart disease (CHD) remains challenging because of its complex morphology. Representing the intricate structures of CHD on conventional two-dimensional flat screens is difficult owing to wide variations in the pathologies. Technological advancements, such as three-dimensional-printed heart models (3DPHMs) and virtual reality (VR), could potentially address the limitations of viewing complex structures using conventional methods. This study aimed to investigate the usefulness and clinical value of four visualization modalities across three different cases of CHD, including ventricular septal defect, double-outlet right ventricle, and tetralogy of Fallot. Seventeen cardiac specialists were invited to participate in this study, which was aimed at assessing the usefulness and clinical value of four visualization modalities, namely, digital imaging and communications in medicine (DICOM) images, 3DPHM, VR, and 3D portable document format (PDF). Out of these modalities, 76.4% of the specialists ranked VR as the best for understanding the spatial associations between cardiac structures and for presurgical planning. Meanwhile, 94.1% ranked 3DPHM as the best modality for communicating with patients and their families. Of the various visualization modalities, VR was the best tool for assessing anatomical locations and vessels, comprehending the spatial relationships between cardiac structures, and presurgical planning. The 3DPHM models were the best tool for medical education as well as communication. In summary, both 3DPHM and VR have their own advantages and outperform the other two modalities, i.e., DICOM images and 3D PDF, in terms of visualizing and managing CHD.